Artificial Intelligence in Education: Literature Review on The Role of Conversational Agents in Improving Learning Experience - Alfehaid, Abdulaziz; Hammami, Mohamed Amin (International Journal of Membrane Science and Technology, 2023)
A growing number of teachers and students are turning to artificial intelligence-powered conversational bots as a means of bolstering and facilitating learning and teaching. Conventional educational agents are intended to do the duties that would normally be carried out by human educators, specifically, providing students with instructions. The purpose of this research is to review the literature on the use of chatbots and conversational agents to promote learning and enhance student engagement. To better understand the complexities of deploying conversational agents for classroom use, it is helpful to first recognize the role that conversational technologies play in facilitating student engagement during learning. The study found credible evidence to support the need for conversational agents in education as teachers grapple with urgency to implement artificial intelligence-based tools and services in classroom and online learning.